LEARNERS’ ERRORS IN WRITING THE RECOUNT TEXT - Gita Khoirunisa; Yanti Suryanti; Cucu Mariam (Pedagogia: Jurnal Ilmiah Pendidikan, 2021)
The objective of this research was to identify and to analyze what are kinds of grammatical errors made by the eighth-grade learners when they wrote the recount text. The design of this research was descriptive research design. The population of this research was the 8C learners of SMP Negeri 8 Bogor and the number of the sample was 31 learners. The researcher used three methods for getting the data; they were data from documentation, data from questionnaire, and data from the interview. The result of this research indicated that the 8C learners of SMP Negeri 8 Bogor had poor ability in writing the recount text. The highest percentage errors were made in the simple past tense by 83.8%, the second one was using in subject-verb agreement by 67.7%, the third one was preposition by 32.2%, and the last errors was pronoun 16.1%. Furthermore, based on the result of the questionnaire, most of the learners responded that they felt difficult in constructing grammatical sentences especially in the use past tense and it was appropriate with the result of the learners’ work and the answer of the interview. In the current research, errors in past tense was more dominant than errors in subject verb agreement, errors in preposition, and errors in pronoun.